PENGARUH KUALITAS PELAYANAN DAN HARGA TERHADAP KEPUTUSAN PEMBELIAN RUMAH MAKAN BERINGIN EDDY PEKANBARU - -, Apriadi - (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2024)
This research aims to find out whether service quality influences purchasing decisions at Beringin Eddy Pekanbaru Restaurant. To find out whether price influences purchasing decisions at Beringin Eddy Pekanbaru Restaurant. To find out whether service quality and price influence purchasing decisions at Eddy Eddy's Beringin Restaurant in Pekanbaru. Hypothesis testing uses the SPSS Version 25.00 statistical test tool. The data analysis method uses path analysis. The results of the research are that service quality has a significant effect on purchasing decisions. Price does not have a significant effect on purchasing decisions. Service Quality and Price have a significant influence on Purchasing Decisions. Keywords : Quality Service , Price, Purchase Decision